Manure evaluation in dairy cows - Steen, Katarina (2005)
Manure evaluation has been suggested as a cheap, fast and easy method which can give information about the digestibility of the ration, the function of the rumen, where in the gastrointestinal tract the feed is digested and the health of the cow.